Creditor’s arrears and payment by consignment in the law of Peru and Argentina - Alferillo, Pascual Eduardo (2024)
The regulation of ‘arrears of the creditor’ and ‘payment by consignment’ is analyzed in the Peruvian Civil Code and in the Argentine Civil and Commercial Code, in this sense, it is possible to compare the requirements for the design, origin and effects of each of these figures in the prevailing legislation.This method allows to see the evolution of the connection between the institutions to visualize the possible solutions that perfect their harmonious assembly in the context of the 40th anniversary of the Peruvian Civil Code.